Phosphorus Adsorption and Its Correlation with Physicochemical Properties of Volcanic-Influenced Soils of Meupi-Awing in Northwest Cameroon - Mofor Nelson Alakeh; Njoyim Estella Buleng Tamungang; Fai Joel Alongifor (Applied and Environmental Soil Science)
This study evaluated the physicochemical properties and phosphorus adsorption characteristics of surface soils (0–30 cm) of Meupi on the flank of Mount Lefo-Awing. In volcanic-influenced soils, usually characterized by high acidity, phosphorus is often not readily available to plants, and this deficit tends to limit plant growth. Soil physicochemical properties and phosphorus adsorption studies were carried out using standard techniques. Results of soil physicochemical studies showed that the soils were strongly acidic (pH ranged from 4.7 to 5.1), with low available phosphorus (5.47 to 6.97 mg/kg). The apparent equilibrium time for phosphorus to be adsorbed in the analyzed soils was 24 hours. Phosphorus sorption studies revealed that the rate of phosphorus adsorption increased with an increase in the concentration of added phosphorus but decreased at a certain level at higher concentrations because the soil had no more capacity to adsorb phosphorus. The degree of fitness (R2) of the phosphorus adsorption data for the different adsorption models was in the order Langmuir < Temkin < Van Huay < Freundlich. This suggested that the Freundlich isotherm model was the best fit to describe P sorption processes in soils. The pseudo-second-order kinetics model, which assumed that the rate of phosphorus sorption was dependent on the number of active sites, gave a good fit to predict and describe the kinetics of phosphorus sorption from the soil solution. The capacity of the soil to adsorb phosphorus significantly correlated positively with amorphous Fe (r = 0.953 and p<0.05), free Fe (r = 0.984, 0.976 and p<0.05), free Al (r = 0.994 and p<0.01, r = 0.988 and p<0.05), and clay (r = 0.968 and p<0.05), which were the main parameters considered as predictors of phosphorus adsorption activities in the soils.